Corporate realities : the dynamics of large and small organisations - Goffee, Robert. (Routledge, 1995)
This book is about: The traditional entrepreneurial firm; Managing the creative and professional small business; From small to large: handling entrepreneurial growth; Manufacturing organisations; ...